Kajian Kepribadian Presiden Perancis Emmanuel Macron Menggunakan Level Analisis Individu - Puspitarini, Renny candradewi; Afkarin, Sofiatul (State Islamic Institute of Kudus (IAIN Kudus), 2018)
Individual Level Analysis of France President Emmanuel Macron. This paper is the result of an individual level analysis study conducted to explain qualitatively the personality, motivation and beliefs of French President Emmanuel Macron. This study employs qualitative data consisting of event data collected from various news sources with exclusionof exclusive interviews and state speeches and studied since Emmanuel Macron was inaugurated as President of France on May 17, 2017. Explanations regarding personality, motivation and beliefs assist to compile the rationality built on the record of educational background, family background, personality also helps to identify the relationship between leadership styles, motivation for decisions and actions that reflect the direction of French foreign policy. While beliefs are recognized through statements and answers given by for questions raised by journalists or foreign journalists in certain situations. This paper using a framework of individual analysis studies by Valerie Hudson, Jerrold Post and Margaret Hermann, it is concluded that Emmanuelle Macron is classified as a type of leader who is inconsistent with the characteristics of expansionist ambitions, high information complexity, good level of diplomatic knowledge or training and always had a consideration to invite other countries to establish harmonious and strategic relations with France.Keywords: individual level analysis, leadership type, conciliatory leadership type, foreign policy analysis